2021
DOI: 10.3390/molecules26103000
|View full text |Cite
|
Sign up to set email alerts
|

D-Sorbitol Physical Properties Effects on Filaments Used by 3D Printing Process for Personalized Medicine

Abstract: Fused filament fabrication (FFF) is a process used to manufacture oral forms adapted to the needs of patients. Polyethylene oxide (PEO) filaments were produced by hot melt extrusion (HME) to obtain a filament suitable for the production of amiodarone hydrochloride oral forms by FFF 3D printing. In order to produce personalized oral forms adapted to the patient characteristics, filaments used by FFF must be controlled in terms of mass homogeneity along filament. This work highlights the relation between filamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
(87 reference statements)
3
4
0
Order By: Relevance
“…The 5-ASA did not show signs of thermal decomposition until reaching approximately 230 °C (T max 292 °C). These data are also in accordance with previous reports [ 15 , 39 , 52 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The 5-ASA did not show signs of thermal decomposition until reaching approximately 230 °C (T max 292 °C). These data are also in accordance with previous reports [ 15 , 39 , 52 ].…”
Section: Resultssupporting
confidence: 94%
“…The sorbitol remained thermally stable until it was heated to ~250 • C, with its maximum degradation at 357 • C. The 5-ASA did not show signs of thermal decomposition until reaching approximately 230 • C (T max 292 • C). These data are also in accordance with previous reports [15,39,52].…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 94%
See 1 more Smart Citation
“…It has been reported that the decomposition of d -sorbitol starts at 200 °C. 40 The DSC data of the membrane containing triethanolamine, cellulose acetate, sorbitol, and acetone are shown in Fig. S2,† where 3 endothermic peaks at 127, 206, and 274 °C and 1 exothermic peak at 337 °C can be seen, which could be related to the boiling of triethanolamine, a phenomenon that occurs at 335 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, additive manufacturing (AM), or 3D printing, is widely applied in many areas of science and technology, such as medicine [ 39 , 40 , 41 , 42 , 43 , 44 ], engineering [ 45 , 46 , 47 , 48 ], and material sciences [ 49 , 50 , 51 , 52 , 53 ]. In chemistry, 3D printing improves process efficiency by manufacturing fluidics [ 54 , 55 , 56 ], customized reactors for organic synthesis [ 57 , 58 , 59 , 60 , 61 ], and specific catalytic devices [ 62 , 63 , 64 ].…”
Section: Introductionmentioning
confidence: 99%